2018
DOI: 10.1016/j.laa.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Equiangular tight frames that contain regular simplices

Abstract: An equiangular tight frame (ETF) is a type of optimal packing of lines in Euclidean space. A regular simplex is a special type of ETF in which the number of vectors is one more than the dimension of the space they span. In this paper, we consider ETFs that contain a regular simplex, that is, have the property that a subset of its vectors forms a regular simplex. As we explain, such ETFs are characterized as those that achieve equality in a certain well-known bound from the theory of compressed sensing. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 63 publications
(283 reference statements)
0
58
0
Order By: Relevance
“…There seems to be evidence that a stronger result than Theorem holds, namely, that for p an odd prime, AGfalse(2,p2false) contains no copies of AG(2,p2). We note that by applying [, Theorem 5.2] to [, Theorem 5.1] over a finite field of order p2, we may obtain an equiangular tight frame of p4 vectors spanning a space of dimension p2false(p21false)/2 which has a binder which contains AG(2,p2). However, one may verify via triple products that these equiangular tight frames are not switching equivalent.…”
Section: A Family Of Gabor Equiangular Tight Frames Associated With Bmentioning
confidence: 99%
See 1 more Smart Citation
“…There seems to be evidence that a stronger result than Theorem holds, namely, that for p an odd prime, AGfalse(2,p2false) contains no copies of AG(2,p2). We note that by applying [, Theorem 5.2] to [, Theorem 5.1] over a finite field of order p2, we may obtain an equiangular tight frame of p4 vectors spanning a space of dimension p2false(p21false)/2 which has a binder which contains AG(2,p2). However, one may verify via triple products that these equiangular tight frames are not switching equivalent.…”
Section: A Family Of Gabor Equiangular Tight Frames Associated With Bmentioning
confidence: 99%
“…The following theorem is a specific application of [, Theorem 6.2], which generalizes [, Section 2.4], but we will prove it here directly with Lemma and state it within the context of spectrahedron arrangements. Theorem Let m=(m0,,ms) be a vector of odd integers 3 with false|mfalse|==0sm and construct G(m) with binder scriptB.…”
Section: Spectrahedral Arrangements From Binders Of Equiangular Tightmentioning
confidence: 99%
“…In Theorem 3.5, we then characterize when the subspaces spanned by these simplices form a special type of ECTFF known as an equi-isoclinic tight fusion frame (EITFF). This occurs for some, but not all, of the ETFs considered in [20]. We further show that every difference set that produces an EITFF in this way also yields a complex circulant conference matrix C, namely an (S + 1) × (S + 1) circulant matrix whose diagonal entries are zero, whose off-diagonal entries are unimodular and for which C * C = SI.…”
mentioning
confidence: 76%
“…It was recently shown that certain harmonic ETFs are comprised of regular simplices [20]. To see this from basic principles, let D be a D-element difference set in an abelian group G of order G,…”
Section: Fine Difference Setsmentioning
confidence: 99%
See 1 more Smart Citation